2020
DOI: 10.1002/iid3.376
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interferon‐α expression in plasmacytoid dendritic cells in asthma

Abstract: Background Toll‐like receptor (TLR)‐7‐associated rhinovirus (RV) activation is involved in the pathogenesis of asthma. Plasmacytoid dendritic cells (pDCs) are the main interferon‐α‐producing cells against viruses. Objective To determine whether asthmatic patients and control subjects differ in terms of interferon‐α expression in pDCs under TLR‐7 or RV stimulation. Methods pDCs were identified in BDCA‐2+ and HLA‐DR+ peripheral blood mononuclear cells. Interferon‐α expression of pDCs was analyzed after TLR‐7 sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In several studies, deficiency of various IFN has been verified utilizing cultured human bronchial epithelial cells (HBECs) from asthmatics after RV infection in vitro , which leads to the deficiency of IFN-β and IFN-λ in primary bronchial epithelial cells (PBECs) and deficiency of IFNs (γ, α, β and λ) and IL-15 in bronchoalveolar lavage (BAL) cells ( 23 ). This result is accorded with that of Lin et al, showing the feasibility of utilizing IFN for alleviating RV infection ( 106 ).…”
Section: Utilizations Of Anti-inflammatory Cytokinessupporting
confidence: 90%
“…In several studies, deficiency of various IFN has been verified utilizing cultured human bronchial epithelial cells (HBECs) from asthmatics after RV infection in vitro , which leads to the deficiency of IFN-β and IFN-λ in primary bronchial epithelial cells (PBECs) and deficiency of IFNs (γ, α, β and λ) and IL-15 in bronchoalveolar lavage (BAL) cells ( 23 ). This result is accorded with that of Lin et al, showing the feasibility of utilizing IFN for alleviating RV infection ( 106 ).…”
Section: Utilizations Of Anti-inflammatory Cytokinessupporting
confidence: 90%
“…Consistently, a in IFN type I production was observed in patients in which RV was detected in vivo compared to patients without RV in their airways. For the latter group the IFN-a detection was significantly lower (19). In preschool asthmatic children, the same deficiency was found during a nonsymptomatic phase, however during HRV-induced exacerbations there is a delayed, but sufficient IFN-a production measurable (90,92).…”
Section: Interferon Type Imentioning
confidence: 60%
“…Those patients showed a temporal upregulation of IFN-a and IFN-g levels, which also correlated with the clinical parameters assessed by Cold Symptoms Score (CSS) (94). In pDCs as well as in PBMCs it has been shown that TLR-7/8-agonists, for example Resiquimod, and RV infection lead to an upregulation of IFN type I, however in asthmatic patients, this upregulation was found to be deficient (19,95). In infants deficiency in IFN type I production in the first place, also caused increased susceptibility to RV infections and thereby to a higher risk of subsequent asthma development (96).…”
Section: Interferon Type Imentioning
confidence: 68%
See 1 more Smart Citation
“…Plasmacytoid dendritic cells (pDCs) are the primary cells responsible for producing IFN-α against viruses. Lin et al ( 2020 ) found that after RV stimulation, interferon-α production by pDCs was significantly increased in normal subjects but not in asthmatic patients. This provides further evidence of a defective innate response to RV infection in asthmatic patients.…”
Section: The Role Of Gut Microbial Changes Caused By Respiratory Infe...mentioning
confidence: 99%